Corporate social responsibility in hotels: a stakeholder approach - Farmaki, Anna (My University, 2018)
Purpose: This study aims to examine stakeholder interests in and influence on corporate social responsibility (CSR) implementation in hotels through an instrumental stakeholder theory lens. Design/methodology/approach: Semi-structured interviews with 54 managers from several sectors of the Cyprus tourism industry were undertaken using purposive sampling. Findings: There is a dominance of supply-chain stakeholder interests which in turn outline the CSR orientation of hotels, whereas stakeholder influence, largely shaped by the interdependent, multi-faceted nature of the tourism industry, conditions the implementation of CSR in hotels. Interestingly, stakeholder influence on CSR in hotels is not corresponding to stakeholders’ perceived saliency, indicating that stakeholder analysis needs to move beyond the consideration of salient stakeholders’ interests. Research limitations/implications: Although the focus of this study has been the perceptions of tourism stakeholders in Cyprus, the exploratory approach adopted in the study sets the ground for further research to consider stakeholder issues regarding CSR in hotels from an instrumental perspective. In addition, insights from this study might inform practitioners in similar destinations. Originality/value: In encouraging a holistic approach to strategic CSR in hotels, this study contributes a framework of stakeholder roles, emanating from stakeholder responsibility and stakeholder involvement in CSR in the hotel sector that will be of interest to both academics and practitioners.
Keywords: Hotels; Corporate social responsibility; Stakeholder theory